Cannabidiol potentiates phenobarbital effects in the control of pentylenetetrazole (PTZ)-induced epileptic seizures in neonate rats - Pinto, Lillian Soares; Oliveira, Matheus Silva de; Borges, Giovanna Bruno; de Castro, Olagide Wagner; Moreira, Fabrício de Araújo; Santos, Victor Rodrigues (Frontiers in Pediatrics, 2025)
Epilepsy is characterized by the predisposition to epileptic seizures resulting from neuronal hyperexcitability and hypersynchrony. Seizure management consists primarily of the long-term use of antiseizure drugs, such as phenobarbital (PB). However, many patients, especially neonates, exhibit resistance to PB and can suffer adverse effects, including abnormal neuronal apoptosis. Cannabidiol (CBD), a non-psychotomimetic phytocannabinoid CBD has demonstrated efficacy in attenuating epileptic seizures. However, its interaction with PB remains largely unexplored. This study investigated the potentiation effect of CBD on PB in a neonatal pentylenetetrazole (PTZ)-induced seizure model. Ten-day-old (P10) Wistar rats were intraperitoneally pretreated with PB (3, 10, 30, 50, or 75 mg/kg) and/or CBD (3, 30, 100, or 200 mg/kg). After 60 min, seizures were induced by subcutaneous administration of PTZ (100 mg/kg), and seizure latency, duration, and severity were subsequently assessed. Low doses of CBD (3 and 30 mg/kg) exhibited limited efficacy when administered alone, while higher doses (100 and 200 mg/kg) modestly attenuated PTZ-induced seizures. However, CBD (30, 100, or 200 mg/kg) significantly enhanced the efficacy of a subeffective dose of PB (10 mg/kg). These results indicate a dose-dependent potentiation by CBD of PB effects, supporting the potential of CBD as an adjunct therapy for neonatal seizures.